Demokratische Resilienz als Konzept - Wolfgang Merkel (Normative Konstituenzien der Demokratie, 2024)
Resilience has risen to become a key concept in science and society. Resilience is used in many scientific disciplines as diverse as materials science, architecture, engineering , psychology, sociology, sustainability science, and now, for some years, political science too. More generally, resilience means the ability of an object or a system to withstand external and internal disturbances, impositions, and shocks without giving up its fundamental structures and functions. Democratic resilience enables transformation but prevents systemic change. As a scientific concept, democratic resilience is, on the one hand, an analytical category that seeks to grasp empirically ,,what is“ (what resilience potential does a given democratic system have?) and, on the other hand, postulates normatively ,,what should be“ (what is a desirable resilient democracy and how can it be established?). The empirical and the normative dimensions of the concept of resilience must be kept apart. This applies not least to democracy research.
Keywords: 300